Electronic transaction of internet banking and its perception of Malaysian online customers - Haque, A. K. M. Ahasanul; Tarofder, Arun Kumar; Rahman, Sabbir; Raquib, Md. Abdur (Academic Journals, 2009)
The purpose of this research is to find out significant factors of consumers’ perception on e-banking transaction by Malaysian bank consumers. The study utilizes a combination of theoretical frameworks and quantitative techniques o testify the statistical relationships between consumer perceptions on e-banking transaction. Meanwhile factor analysis was performed to extraction and make initial decision on the number of factors underlying asset of measured variables of interest. Thereafter structural equation mode (SEM) was estimated to anticipate the effects of the explanatory variables. This study shows that only protected transaction, have significant impact on consumers’ perception about e-banking security, followed by service quality and regulatory frame work issues. This study is the first that seeks to ascertain the insight into e-banking in Malaysia, which has not been previously been investigated and much statistical significance makes this study a potential cornerstone for future research. Therefore, this study thus sets an important benchmark for further research in the area.